Don't we need diagnostic facilities for genetically determined diseases? (Bangladesh Journal of Medical Biochemistry, 2013)
DOI: http://dx.doi.org/10.3329/bjmb.v6i1.13279Bangladesh J Med Biochem 2013; 6(1): 3-4